Insulin Resistance, Adiponectin, and Dyslipidemia as Key Determinants of Metabolic and Reproductive Dysregulation in Polycystic Ovary Syndrome - Krarr Haider Haddawi; Bushra Raouf Yaseen; Redha Dawud Abd Alredha; Kareem Obayes Handool (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Polycystic ovary syndrome (PCOS) is a common endocrine disorder associated with insulin resistance, dyslipidemia, and metabolic dysfunction. However, the predictive value of insulin resistance (HOMA-IR), dyslipidemia, and adiponectin in identifying PCOS and stratifying metabolic risk remains unclear, particularly in underrepresented populations, such as Iraqi women. This study evaluated these parameters to improve risk stratification and early intervention strategies in resource-limited settings.METHODS: This case-control study included 100 women (50 with PCOS diagnosed using the Rotterdam criteria and 50 age-matched healthy controls). Anthropometric and clinical assessments, including BMI and hirsutism scores, were performed. Fasting blood samples were analyzed for glucose and lipid profile using colorimetric assays, insulin via electrochemiluminescence immunoassay (ECLIA), and adiponectin via enzyme-linked immunosorbent assay (ELISA), and HOMA-IR was calculated to quantify insulin resistance.RESULTS: Women with PCOS exhibited significantly higher BMI, fasting glucose, insulin, and HOMA-IR values (p<0.001 for all) than controls. Dyslipidemia was evident, characterized by elevated total cholesterol, LDL-C, and triglyceride levels, as well as lower HDL-C levels (p<0.001). Adiponectin levels were markedly reduced in the PCOS group (p<0.001) and showed strong inverse correlations with HOMA-IR (r=–0.554, p<0.001) and fasting insulin (r=–0.453, p<0.001). Logistic regression indicated that HOMA-IR was the most significant predictor of PCOS (OR=28, 95% CI 4.86–161.44, p=0.0002), whereas higher adiponectin levels offered significant protective effects (OR=0.54, 95% CI 0.36–0.82, p=0.0039).CONCLUSION: Insulin resistance, dyslipidemia, and low adiponectin levels are strongly associated with PCOS and metabolic dysfunction in Iraqi women. HOMA-IR is a key predictor, whereas adiponectin may have protective effects. These findings highlight the potential of these biomarkers in risk stratification and early intervention in resource-limited settings.KEYWORDS: PCOS, adiponectin, HOMA-IR, dyslipidemia